Non-lesional late-onset epilepsy in the elderly Japanese patients: Presenting characteristics and seizure outcomes with regard to comorbid dementia. (September 2022) - Nagino, Naoto; Kubota, Yuichi; Nakamoto, Hidetoshi; Miyao, Satoru; Kodama, Tomohiro; Ito, Susumu; Oguni, Hirokazu; Chernov, Mikhail
Highlights: Non-lesional late-onset epilepsy in the elderly has variable presenting features. In this population, comorbid dementia has been diagnosed in 35% of cases. Seizure-free status for ≥ 12 months has been attained in 72% of patients. Seizure-free status is often attained with the low-dose antiseizure monotherapy. Comorbid dementia is associated with worse response to antiseizure therapy. Abstract: The objective of the present retrospective study was analysis of clinical, radiological, and electrophysiological characteristics of the non-lesional late-onset epilepsy (NLLOE) in the elderly Japanese patients, and comparison of the seizure outcomes in this population with regard to presence of comorbid dementia. The study cohort comprised 89 consecutive patients with NLLOE aged ≥ 65 years. In 49 cases (55%), NLLOE manifested with a single type of seizure. Focal impaired awareness seizures (FIAS) were encountered most often (in 69 patients; 78%). Ten patients (11%) had a history of the status epilepticus. Comorbid dementia was diagnosed in 31 patients (35%). Localized or diffuse white matter hyperintensity was the most common imaging finding (66 cases). Epileptiform discharges in the temporal area represented the most frequent abnormality on interictal EEG (24 cases). Seizure-free status for ≥ 12 months was attained in 46 out of 64 patients (72%), who were followed for ≥ 12 months (range, 12 – 110 months), and 42 of them received monotherapy, mainly with levetiracetam (21 patients), carbamazepine (10 patients), or lacosamide (8 patients). In comparison to their counterparts, the rate of seizure-free status for ≥ 12 months was significantly lower in patients with comorbid dementia (81% vs. 52%; P = 0.0205). In conclusion, the NLLOE among Japanese patients aged ≥ 65 years has variable presenting characteristics, and comorbid dementia is diagnosed in one-third of cases. Seizure-free status for ≥ 12 months may be attained in more than two-thirds of treated patients, but comorbid dementia is associated with significantly worse response to antiseizure therapy.